Effectiveness of Mechanical Endovascular Thrombectomy in a Model System of Cerebrovascular Occlusion - Chueh, J.Y. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: A number of thrombectomy devices are currently undergoing clinical evaluation; meanwhile, various novel devices are under investigation. The aims of this study were to quantify flow restoration and the particle size distribution of the effluent pursuant to MET in an in vitro occlusion model. MATERIALS AND METHODS: The model system was composed of 3 elements: an ICA/MCA replica, a clot model with mechanical properties similar to those of thrombi found in patients at risk of stroke, and a pulsatile flow loop. Different thrombectomy mechanisms including mechanical retrieval, aspiration, and waveguide induced cavitation were used. The efficacy end points were recanalization rate and amount of flow restoration. The risk of the embolic shower was assessed to evaluate device safety. RESULTS: The recanalization rates were the following: Merci, 67%; Solitaire, 100%; Penumbra, 83%; Enterprise, 17%; and the waveguide, 0%. In experiments in which recanalization was achieved, the amount of flow restoration for the Merci, Solitaire, and Enterprise devices was 100%, 92%, and 86%, respectively. The mean sizes of generated small and large clot fragments were between 23 and 37 and 215 and 285 μm, respectively, depending on the device used. The Merci device generated the fewest number of large fragments compared with the Penumbra system (P < .05) and Solitaire (not significant). CONCLUSIONS: The risk of embolic shower was influenced by the mechanism of action for the thrombectomy device. Clinically reported recanalization rates for the Solitaire, Penumbra, and Merci devices were nearly identical in this model system, suggesting that this model may provide a predictive tool for preclinical evaluation of MET.